p ∧ T ≡ pp ∨ F ≡ p
To understand and prove the given expressions, we will use the following properties of logical equivalences:
1
To understand and prove the given expressions, we will use the following properties of logical equivalences:
1. Identity Law: p ∨ F ≡ p
2. Domination Law: p ∧ T ≡ p
3. Idempotent Law: p ∨ p ≡ p
Now, let’s proceed with proving the given expressions step by step:
Expression 1: p ∧ T ≡ p
Using the Domination Law (Idempotent Law reversed), we have:
p ∧ T ≡ p ∨ F ∧ T
≡ p ∨ (F ∧ T) (Associative Law)
≡ p ∨ F (Identity Law)
≡ p (Identity Law).
Expression 2: pp ∨ F ≡ p
Using the Identity Law, we have:
pp ∨ F ≡ p ∨ p ∨ F
≡ p ∨ F (Idempotent Law)
≡ p (Identity Law).
So we have shown that both the given expressions are true. The logical equivalences hold:
p ∧ T ≡ p
and
pp ∨ F ≡ p.
More Answers:
Understanding the Negation Operator: Reversing Truth Values and Sign in Mathematics and Computer ProgrammingSimplifying If-Else Logic with the Conditional Operator in Programming Languages
The Logic of Conditional Propositions: Understanding the Relationship between Hypotheses and Conclusions in Mathematics